Women's Rights? The Politics of Eugenic Abortion in Modern Japan - Kato, Masae (IIAS Publications Series, 2009)
This volume explores the concept of Japanese reproductive rights and liberties in light of recent developments in disability studies. Masae Kato asks important questions about what constitutes personhood and how, in the twenty-first century, we come to understand eugenic abortion and other bioethical arguments. Tracing the origin and influence of the concept of a "right," the author places the term in local social and historical contexts in order to determine that it still carries overtones of Anglo-American philosophy, rather than universal truth. Digging deeply into Japanese debates on selective abortion, Women's Right? discusses how this charged term can be both de-Westernized and de-masculinized, especially in its appropriations by the Japanese women's movement and disability scholars. This title is available in the OAPEN Library - http://www.oapen.org.